Cultivating Relationality and an Ethics of Care through Arts-Based and Play-Based Research - Hill, Tiffany T.; Wright, Laura; Etmanski, Catherine (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
In this paper, we make practical and theoretical contributions to feminist adult education. Practically, we provide an overview of a three-hour arts- and play-based research workshop with research activities/tools that readers can further research to adapt to their own contexts. Theoretically, we explore how these creative practices can contribute to wider notions of relationality and ethics of care when integrated with Indigenous, decolonising, and intersectional, feminist approaches. After offering a rich description of arts- and play-based methods (photovoice, found poetry, collage, narrative métissage, river journey, and lego visioning), we discuss how creative methods and practices hold the potential to foster deeper connections, promote collective accountability, and support the ongoing work of decolonising education. We encourage future research to further explore the intersection of these practices with feminist adult education, and to continue expanding our collective understanding of how to cultivate care, responsibility, and reciprocity in teaching and learning settings.